'Kasar' community: migration from community business. (24th October 2022) - Vazhapilly, Raju Varghese; Dam, Leena B.
Community businesses have dominated the landscape of Indian business since time immemorial. Business communities of India were smaller communities based on religion or caste. Based on its origin, every business community had governing norms. These norms decided the product or service that the community dealt in. There were religious and social parameters governing the community. One such business community was the 'Kasar' community with major presence in Maharashtra. The community was traders of bangles and metal craft. 'Kasar' community and bangle trading are synonymous in Maharashtra. Bangles are ritually very important in several customs and traditions of India. Once, a thriving community in the bangle trading business, its members are now migrating away from their traditional business. The aim of this study is to analyse the business practises of this community. The study also investigates the possible reasons for shift in calling from traditional business to other opportunities.